The comb structure of apis dorsata F. (hymenoptera: Apidae): 3-dimensional architecture and resource partitioning - Ninat Buawangpong (2018)
© 2014, Chiang Mai University. All rights reserved. The architecture of the comb structure of the giant honeybee Apis dorsata was examined, including cell sizes, comb area, comb volume, and gravimetric capacity. Regardless of comb area, the partitioning of comb between brood rearing and food storage centered around 83% of the comb surface being used for brood production. The potential gravimetric capacity of the total comb was variable displaying a range of 1–2 g per cm2 of comb surface. The largest comb examined would have had a hypothetical weight of ca. 17 kg, while the smallest comb ca. 2.0 kg. These calculations do not include the weight of adult bees. A large colony would possess as much as 8 kg of adult worker bees based on an average worker weight of 160 mg.